ANALISIS KELAYAKAN PENGEMBANGAN USAHA BADAN USAHA MILIK DESA (BUMDes) BERKAT YAKIN BERDASARKAN POTENSI DESADIDESA CIPANG KANAN, KECAMATAN ROKAN IV KOTO, KABUPATEN ROKAN HULU PROVINSI RIAU - Yandi Jefri; Mayes Anthony; Taryono Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the potential of priority villages that can be developed into BUMDes businesses. To find out the financial feasibility of potential village businesses that are a priority to be used as BUMDes businesses. The research method used is a case study research method. The subjects in this study to find out the first objective were 6 farmers, distributors/toke, village apparatus and BUMDes. Data analysis using AHP method and financial feasibility analysis. Based on the results of the study, it can be concluded that 1) The potential of village businesses that can be developed by the Village-Owned Enterprises (BUMDES) Berkat Yakin in Cipang Kanan Village, Rokan IV Koto District, Rokan Hulu Regency, Riau Province is the citronella oil business. From the results of the weighting of the criteria obtained in this study, rubber was 0.147, corn was 0.117 and citronella oil was 0.194. 2) The financial aspects of citronella oil business are: NPV obtained Rp. 469,508,657. This means that the citronella oil business investment is feasible because the NPV value > 0 is Rp. 469,508,657 > 0. Net B/C ratio in citronella oil business in Cipang Kanan Village, Rokan IV Koto District, Rokan Hulu Regency, Riau Province is 1.15. B/C Ratio Value > 1 Business has profitable prospects. The results of the IRR calculation on the citronella oil business were 296%. Based on the calculation of the IRR value above, the IRR value is greater than the 10% interest rate value. So it can be concluded that this business is feasible to develop because the IRR value is greater than the 10% interest rate, meaning that this business is feasible to be developed. The results of the calculation of the Payback Period in the citronella oil business in Cipang Kanan Village, Rokan IV Koto District, Rokan Hulu Regency, Riau Province of = 4 months 3 days. This means that the investment costs can be returned for 4 months 3 days. From the results of the Payback Period calculation above, information can be obtained that the citronella oil business is feasible to run. Based on the results of data analysis, it can be seen that the BEP obtained in the citronella oil business is 6,832. This means that the citronella oil business in producing must produce as much as 6,832 KgKeywords: Village Potential, Financial Feasibility